2006
DOI: 10.1007/s11133-006-9010-4
|View full text |Cite
|
Sign up to set email alerts
|

All the News that’s Fat to Print: The American “Obesity Epidemic” and the Media

Abstract: In the last twenty years scientific, medical, and public health interest in obesity has skyrocketed. Increasingly the term "epidemic" is being used in the media, medical journals, and public health policy literature to describe the current prevalence of fatness in the U.S. Using social scientific literature on epidemics, social problems, and feminist theories of the body, this paper traces the historical emergence of the "obesity epidemic" through an analysis of 751 articles on obesity published in The New Yor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
151
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(170 citation statements)
references
References 12 publications
6
151
0
13
Order By: Relevance
“…Previous research has shown that the news media frame obesity as a moral problem of gluttony and sloth (Boero 2007) and overwhelmingly blame bad individual choices (Saguy and Almeling 2008), despite increasing discussion of social-structural factors over time (Lawrence 2004). Extant work, however, has been limited either analytically-by, for instance, not examining the role of gender, class, or race (Lawrence 2004)-or methodologically, by relying heavily on a small (Boero 2007) or nonrepresentative sample (Saguy and Almeling 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has shown that the news media frame obesity as a moral problem of gluttony and sloth (Boero 2007) and overwhelmingly blame bad individual choices (Saguy and Almeling 2008), despite increasing discussion of social-structural factors over time (Lawrence 2004). Extant work, however, has been limited either analytically-by, for instance, not examining the role of gender, class, or race (Lawrence 2004)-or methodologically, by relying heavily on a small (Boero 2007) or nonrepresentative sample (Saguy and Almeling 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a few scholars have begun examining media reporting on the so-called "obesity epidemic" (Boero 2007;Lawrence 2004;Saguy and Almeling 2008). Natalie Boero (2007) finds that news reporting has largely framed obesity as a moral problem of gluttony and sloth.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is not our point. Nor do we argue that the examples described above constitute the entire critical literature on the obesity epidemic discourse, or comprehensively exemplify its diversity and sophistication (other fine critical work includes Colls, 2006;Guthman and DuPuis, 2006;Boero, 2007). Notwithstanding this range, however, we maintain that, as with the examples discussed above, this broader literature leaves open space for explicit theorisation of the action of emotion.…”
Section: Challenging the 'Epidemic'mentioning
confidence: 87%